PENGUKURAN WAKTU KERJA PADA PEGAWAI DI PABRIK SABLON HELLO PRODUCTION DENGAN METODE WORK FACTOR - Muhammad Ramzy; Devano Belva; Chelsea Regita; Hana Rohadianita (Journal of Optimization System and Ergonomy Implementation, 2025)
This study aims to analyze the measurement of work time for employees at the Hello Production screen printing factory using the Work Factor method. This method is used to identify work time by analyzing the movements and time required to complete a task. Data were collected through direct observation at five workstations: printing, coloring, drying, pressing, and packaging. Each movement and work time were recorded and analyzed using the work factor method to produce work time, normal time, and standard time. The results show that more efficient equipment arrangement and regular skill training can reduce operator fatigue and increase productivity. These findings are crucial for Hello Production management to implement improvement measures in daily operations, ultimately enhancing work efficiency.